The Investment Climate In Post-Conflict Situations - Mills, Rob (The World Bank, 2006)
This paper is a policy review of the role of investment climate in post-conflict situations. It summarizes the broad range of ways in which conflict negatively affects the investment climate, from macroeconomic instability to a degraded regulatory framework. It stresses that attention needs to be paid to the broader "enabling environment," including institutions, governance, capacity, and social capital. It suggests that a vibrant private sector underpinned by a good investment climate is particularly important in the post-conflict recovery phase for three reasons: it generates employment, provides public services where the state has retrenched, and builds social capital. By addressing these important "greed and grievance" factors, the private sector helps reduce the likelihood of a return to conflict. The paper concludes by distilling key lessons relating to the management of the post-conflict reform process. Despite the importance of a good investment climate, greater effort is needed to ensure that private sector development reforms are included in the first round of post-conflict policymaking. Local ownership of reforms and enhanced local capacity to implement them is key to sustainable improvements in the investment climate. Development partners have an important role to play in facilitating dialogue and promoting partnerships between public and private sector stakeholders. At the same time, development partners need to ensure that their presence in fragile post-conflict economies does not damage the very sector they are trying to support